Physically‐based forehead animation including wrinkles. (26th November 2013) - Warburton, Mark; Maddock, Steve
ABSTRACT Physically‐based animation techniques enable more realistic and accurate animation to be created. We present a fully physically‐based approach for efficiently producing realistic‐looking animations of facial movement, including animation of expressive wrinkles. This involves simulation of detailed voxel‐based models using a graphics processing unit‐based total Lagrangian explicit dynamic finite element solver with an anatomical muscle contraction model, and advanced boundary conditions that can model the sliding of soft tissue over the skull. The flexibility of our approach enables detailed animations of gross and fine‐scale soft‐tissue movement to be easily produced with different muscle structures and material parameters, for example, to animate different aged skins. Although we focus on the forehead, our approach can be used to animate any multi‐layered soft body. © 2014 The Authors. Computer Animation and Virtual Worlds published by John Wiley & Sons, Ltd.